(untitled) - Freeman, Roger L. (Hoboken, N.J., 2007)
This book introduce about Chapter devoted to wireless LANs (WLANs) as detailed in IEEE 802.11. Subsections covering IEEE 802.15, 802.16, 802.20, and the wireless metropolitan area network (WMAN). WiFi, WiMax, and UWB applications that have recently experienced explosive growth. Broadband radio in telecommunications, as well as offset frequency division multiplex (OFDM), a new technique for transmitting information in an interference environment. The use of very small aperture satellite terminal (VSAT) systems as an economical alternative to public switched telecommunication networks (PSTN).
Keywords: Radio relay systems,Hệ thống tiếp vận ra-đi-ô; Design and construction,Thiết kế và xây dựng